Effectiveness of chain whispering learning method assisted by online chat messaging - Agung Panji Sasmito; Hani Zulfia Zahro'; Febriana Santi Wahyuni (International Journal of Evaluation and Research in Education (IJERE), 2022)
The online learning process cannot fully explore the potential of students, mainly due to monotonous learning methods. This makes students less enthusiastic in participating in online learning. Students’ learning motivation and achievement become less optimal. This study initiated an alternative online learning method that can be used during the COVID-19 pandemic. This was a research and development (R&D) using ADDIE model with the steps including analysis, design, development, then continued with implementation and ended with evaluation. The learning method developed was the chain whispering method which was carried out online. The developed method was a valid and effective learning method in increasing understanding and motivation.